Multicenter, Phase III Trial Comparing Selenium Supplementation With Observation in Gynecologic Radiation Oncology: Follow-Up Analysis of the Survival Data 6 Years After Cessation of Randomization. (November 2014) - Muecke, Ralph; Micke, Oliver; Schomburg, Lutz; Glatzel, Michael; Reichl, Berthold; Kisters, Klaus; Schaefer, Ulrich; Huebner, Jutta; Eich, Hans T.; Fakhrian, K.; Adamietz, Irenaeus A.; Buentzel, Jens; et al.
Purpose . In 2010, we reported that selenium (Se) supplementation during radiation therapy (RT) is effective for increasing blood Se levels in Se-deficient cervical and uterine cancer patients, and reduced the number of episodes and severity of RT-induced diarrhea. In the current study, we examine whether of Se supplementation during adjuvant RT affects long-term survival of these patients. Patients and Methods . Former patients were identified and questioned with respect to their health and well-being. Results . A total of 81 patients were randomized in the initial supplementation study, 39 of whom received Se (selenium group, SeG) and 42 of whom served as controls (control group, CG). When former patients were reidentified after a median follow-up of 70 months (range = 0-136), the actuarial 10-year disease-free survival rate in the SeG was 80.1% compared to 83.2% in the CG ( P = .65), and the actuarial 10-year overall survival rate of patients in the SeG was 55.3% compared to 42.7% in the CG ( P = .09). Conclusions . Our extended follow-up analysis demonstrates that Se supplementation had no influence on the effectiveness of the anticancer irradiation therapy and did not negatively affect patients' long-term survival. In view of its positive effects on RT-induced diarrhea, we consider Se supplementation to be a meaningful and beneficial adjuvant treatment in Se-deficient cervical and uterine cancer patients while undergoing pelvic radiation therapy.